The Balts - Radiņš, Arnis (Archaeologia Lituana, 2011)
The issue of the Balts in the most ancient written sources is not so simple. Scientists who undertake to research this topic can confirm that. There are various reasons for that, namely, the borders of the writing population reached the Balts comparatively late and the first information about them is rather inaccurate. The ancient and medieval authors can be often characterized by mechanical transfer of already known names to other nations, thereby including the new phenomena in the existing traditional map of the world. Similarly, there are certain interpretation problems present in the process of relating the written sources, archaeological culture, ethnic and language background. [...]